2011
DOI: 10.4103/0970-0218.91334
|View full text |Cite
|
Sign up to set email alerts
|

The study of lipid profile, diet and other cardiovascular risk factors in children born to parents having premature ischemic heart disease

Abstract: Background:Dyslipidemia is a marker for ischemic heart disease (IHD), which can be detected in early childhood and tracks to adulthood. Dyslipidemia, along with factors like diet, obesity and sedentary activity, increases the risk of a child developing IHD in adulthood. Early detection and modification of these risk factors can prevent IHD.Objectives:To study the lipid profile in children born to parents with history of premature IHD and also to study the effect of diet, lifestyle factors, and obesity in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…This was similarly observed in a study conducted by Savitha et al and Webber et al 22,23 Amongst the biochemical parameters, we found that children who were taking CBZ had an increase in their total cholesterol, serum LDL and serum HDL levels and these findings were comparable to that observed by Chuang et al and Kantoush et al 24,25 Similarly, we observed that children, who were on VPA had an increase in their serum cholesterol, HDL and LDL levels which was comparable to the study done by Verrotti et al and a decrease in the levels of triglycerides on follow-up which was also similar to the findings done by Kantoush et al 26,25 The levels of VLDL did not significantly vary as the study progressed which was comparable to other studies. 13,18 The atherogenic indices calculated for any of the four drugs were not significant, which was comparable to the study conducted by Eiris et al and Tekgul et al 18,27…”
Section: Discussionsupporting
confidence: 84%
“…This was similarly observed in a study conducted by Savitha et al and Webber et al 22,23 Amongst the biochemical parameters, we found that children who were taking CBZ had an increase in their total cholesterol, serum LDL and serum HDL levels and these findings were comparable to that observed by Chuang et al and Kantoush et al 24,25 Similarly, we observed that children, who were on VPA had an increase in their serum cholesterol, HDL and LDL levels which was comparable to the study done by Verrotti et al and a decrease in the levels of triglycerides on follow-up which was also similar to the findings done by Kantoush et al 26,25 The levels of VLDL did not significantly vary as the study progressed which was comparable to other studies. 13,18 The atherogenic indices calculated for any of the four drugs were not significant, which was comparable to the study conducted by Eiris et al and Tekgul et al 18,27…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, the mean BMI of the study group (8.79±3.9 kg/m 2 ) was found to be significantly higher than the comparison group (15.92±2.7kg/m 2 ). Present results were comparable with a similar study conducted by Savitha et al 8 The mean BMI in their study was 20.7±3.36 kg/m 2 in the cases and 18.9±2.2 kg/m 2 in the control group. However, in the studies conducted by Dutta et al and Rallidis et al there was no statistically significant difference in the mean BMI values between the two groups.…”
Section: Body Mass Index (Bmi) Comparisonsupporting
confidence: 92%
“…Among all risk factors, total cholesterol is treated as the critical risk factor for IHD. Plaque formation is observed due to changes in arteries present in children and adults [13]. Metabolic syndromes increase the risk of coronary artery disease by 7.3times in males and 10.2 times in female patients [14].…”
Section: Introductionmentioning
confidence: 99%